The Impact of the Implementation of Comprehensive Quality Assurance Standards on Achieving Modern Global Trends in Teaching Science to Public Secondary School Students in Khartoum - Yousif, Taghreed Mohamed Osman Mahmoud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to investigate the impact of the application of comprehensive quality assurance standards in achieving modern global trends in teaching science to public secondary school students in Khartoum. Where the study used the descriptive analytical approach, the study population consisted of science teachers in public schools, and the study also used the questionnaire as a tool for data collection, where (384) questionnaires were distributed, of which (366) were valid for analysis, and the SPSS statistical analysis package was used to analyze the data and hypotheses. The study concluded that there are a set of results, the most important of which is the existence of a statistically significant effect of the application of comprehensive quality assurance standards in achieving global trends in government secondary schools in Khartoum. The results of the study also showed that there is a statistically significant effect of the dimensions of total quality (school management, empowerment of science teachers, and continuous improvement) on modern global trends in teaching science for students of government secondary schools in Khartoum. In the light of the study, several recommendations were made, the most important of which is that public secondary schools in Khartoum continue to apply total quality standards as a tool and technique to acquire and maintain competitive priorities. It is highly competitive, and focusing on science teachers because of its importance in enhancing their performance in a productive way for the benefit of schools. It is also recommended to conduct similar studies in different countries, especially in Arab countries.
Keywords: Comprehensive Quality Standards; Government Secondary Schools in Khartoum; Science Teachers; Modern Global Trends